Introducing finite arithmetics in high school algebra - Acelajado, Maxima Joyosa 1946- (s.n.], 1971)
This paper presents a proposed unit on Finite Arithmetics to be incorporated in the high school Algebra. It is essentially composed of a unit divided into three sub units namely: the modular arithmetic system; finite arithmetics as number systems; and the applications of the congruence module m to test for divisibility by 2,3,4,5,6,7,8,9, and 11. Time allotment for each sub unit is also provided so as to direct discussion.